2016
DOI: 10.1002/jcla.22094
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin serum concentrations are correlated with the severity of knee osteoarthritis

Abstract: Serum and SF myostatin concentrations were correlated with the presence and severity of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Recent reports point out a decreased concentration of serum myostatin in the acute phase and a reverse effect in the chronic phase of burn patients [ 37 , 38 ]. Zhao et al [ 39 ] revealed that serum myostatin levels are higher in patients with knee osteoarthritis. Baczek et al [ 40 ] pointed out the difficulties in interpreting myostatin levels in various disease statuses and in understanding the interrelationship between physiological variables (such as age, sex and physical activity).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports point out a decreased concentration of serum myostatin in the acute phase and a reverse effect in the chronic phase of burn patients [ 37 , 38 ]. Zhao et al [ 39 ] revealed that serum myostatin levels are higher in patients with knee osteoarthritis. Baczek et al [ 40 ] pointed out the difficulties in interpreting myostatin levels in various disease statuses and in understanding the interrelationship between physiological variables (such as age, sex and physical activity).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its potential role in the aforesaid disorder, myostatin could be investigated regarding the prediction of the long-term muscle strength, as well as the therapy improving condition of patients after severe burn injuries. Research by Zhao et al, proved that serum myostatin levels are higher in patients with knee osteoarthritis [ 160 ]. A novel finding made by Su et al, demonstrated in vivo that overexpression of myostatin induces robust expression of TNF-α in rheumatoid arthritis synovial fibroblasts, leading to chronic synovitis [ 161 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…In skeletal muscle, BDNF is involved in the regulation and survival of motoneurons, in the development and differentiation of myoblasts, in the interaction between immune cells and muscle cells (43). However, myostatin and follistatin are altered in osteoarthritis (44, 45), GDF-15 in cardiovascular disease (46), and BDNF in mood disorders (47) and deregulated heart autonomic system (48).…”
Section: Biomarkers Of Sarcopeniamentioning
confidence: 99%